Increasing student engagement and retention using multimedia technologies video annotation, multimedia applications, videoconferencing and transmedia storytelling - Wankel, Laura A.; Blessinger, Patrick (Cutting-edge technologies in higher education, 2013)
Increasing Student Engagement and Retention Using Multimedia Technologies: Video Annotation, Multimedia Applications, Videoconferencing and Transmedia Storytelling examines new research on how videoconferencing, video annotation, video mapping, and related technologies are being used in higher education to increase learner engagement in an epoch of increasing globalization and diversity. These enabling technologies are reshaping and reframing the practice of teaching and learning in higher education. Through case studies, surveys, and literature reviews, this volume will examine how video, mapping, and related technologies are being used to improve writing/publishing skills, academic literacies in students, and create engaging communities of practice through digital storytelling, narratives, and inter-culturalism. This volume will also discuss a framework for deploying and assessing these technologies.